The Development of a Cooperative Learning Model Using Educandy for Vocabulary Instruction at State Islamic Primary School 1 South Tangerang - Elta Dwi Prasepti; Muhbib Abdul Wahab; Wati Susiawati (Prodi Pendidikan Bahasa Arab, Universitas Muhammadiyah Tangerang, 2025)
The researcher selected this topic based on the need to develop a learning model that supports vocabulary acquisition and aligns with students' needs. Students face difficulties in learning vocabulary, such as the limited variety of instructional media, particularly technological tools, reliance on traditional methods, and low motivation, which hinder the optimal achievement of educational objectives. This study aims to explore the development process, validity, and effectiveness of a cooperative learning model, specifically the Teams Games Tournaments (TGT) type, utilizing Educandy for vocabulary instruction. The researcher employed the Research and Development (R&D) methodology, following the ADDIE model developed by Raiser and Molenda. This model consists of five phases: Analysis, Design, Development, Implementation, and Evaluation. The data collection instruments used in this study included tests (pre-test and post-test), questionnaires, interviews, and observations. For data analysis, the researcher applied the Likert scale and the N-Gain test. The findings indicated that the cooperative learning model of the Teams Games Tournaments type, integrated with Educandy, demonstrated a